2019
DOI: 10.1002/jso.25669
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the surgical treatment of pathological proximal femur fractures in the United States

Abstract: Background and objectives Large scale data on the treatment of pathologic proximal femur fractures (PPFFs) are lacking. The purpose of this study was to evaluate trends in patient demographics, complication rates, and relative utilization rates of various techniques associated with PPFFs. Methods The American College of Surgeons‐National Surgical Quality Improvement Program (NSQIP) database was queried for PPFFs from 2009 to 2017. Patient demographics, 30‐day complications, and utilization rates were recorded.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Despite the fact that that prosthesis surgery is the preferred surgical method for patients with a life expectancy of more than 6 mo, treatment of a lesion in the upper metaphyseal region and the life expectancy of MBD patients is possibly increasing. Varady et al[ 39 ] found a trend towards the increased use of IM-nails in patients operated between 2009-2017, indicating a possible change in general treatment strategies (Figures 1 and 2 ).…”
Section: Methods and Outcome Of Surgical Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that that prosthesis surgery is the preferred surgical method for patients with a life expectancy of more than 6 mo, treatment of a lesion in the upper metaphyseal region and the life expectancy of MBD patients is possibly increasing. Varady et al[ 39 ] found a trend towards the increased use of IM-nails in patients operated between 2009-2017, indicating a possible change in general treatment strategies (Figures 1 and 2 ).…”
Section: Methods and Outcome Of Surgical Treatmentmentioning
confidence: 99%
“…In the humerus, pathological fractures of the diaphysis are the most common reason for surgery. As in the femur, IM nailing and prosthesis surgery have the lowest reported reoperation rates and most reoperations are due to non-union, with an increasing complication rate over time[ 37 , 39 ]. The distal third of the humerus accounts for the highest complication rates[ 37 ].…”
Section: Methods and Outcome Of Surgical Treatmentmentioning
confidence: 99%
“…Studies focused solely on impending fractures were ignored and articles on bisphosphonate fractures were excluded: the main entities considered in this study are listed in Table I. Six additional items were identified through other sources, so that 14 articles [29][30][31][32][33][34][35][36][37][38][39][40][41][42] were finally considered pertinent for the aim of the study. Very few studies focused on the preoperative management of these patients, while almost none concentrated on the timing for surgery.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of an impending fracture, prophylactic stabilization of the femur may be indicated not only to reduce pain but also to prevent future fracture. 2,3 Patients with impending fracture that undergo prophylactic stabilization generally do well with a marked reduction in pain while those that suffer a pathological fracture have a marginally higher complication rate owing to a more difficult operation. 1,3,4 Many factors need to be considered before prophylactic intervention, including the potential risk for fracture and patient prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of a pathological fracture, surgery is indicated with the aim of reducing pain and restoring mobility as swiftly as possible, thereby avoiding the risks of prolonged recumbency. In the case of an impending fracture, prophylactic stabilization of the femur may be indicated not only to reduce pain but also to prevent future fracture 2,3 . Patients with impending fracture that undergo prophylactic stabilization generally do well with a marked reduction in pain while those that suffer a pathological fracture have a marginally higher complication rate owing to a more difficult operation 1,3,4 …”
Section: Introductionmentioning
confidence: 99%